Le critère de la primauté de la grâce et de la beauté dans le Directoire pour la Catéchèse (2020). Quelles implications pour la catéchèse et les catéchistes? The criterion of the primacy of grace and beauty in the Directory for Catechesis: what are the implications for catechesis and catechists? - Ilunga, Nkulu Albertine (Rivista di Scienze dell’Educazione, 2025)
Paragonato ai due Direttori catechetici precedenti, il nuovo Direttorio per la Catechesi inserisce tra i criteri per l’annuncio del messaggio cristiano nella catechesi, il criterio del primato della grazia e della bellezza. Una tale novità non può che suscitare domande quali: cosa vuol sottolineare il nuovo Direttorio riguardo a questo criterio. Quali potrebbero essere le implicazioni del rispetto di questo criterio nella catechesi e per i catechisti? È a queste due domande che il presente articolo tenta di rispondere. Compared to the two previous Catechetical Directories, the new Directory for Catechesis includes the criterion of the primacy of grace and beauty among the criteria for the proclamation of the Christian message in catechesis. Such a novelty cannot but raise questions such as: What does the new Directory want to emphasize regarding this criterion? What could be the implications of respecting this criterion in catechesis and for catechists? This article will attempt to respond to these two questions. A diferencia los dos Directorios catequéticos anteriores, el nuevo Directorio para la catequesis introduce entre los criterios para el anuncio del mensaje cristano en la catequesis, el criterio del primado de la gracia y de la belleza. Dicha novedad no puede sino suscitar interrogantes tales como: ¿cuáles serían las implicaciones del respeto de este criterio para la catequesis y para los catequistas? Este artículo intenta dar respuesta precisamente a estas dos cuestiones.